Compressive Behaviours of Oil Bean Shell and Wood Particulates/ Epoxy Composite Board - , E. D. Edafiadhe; , O. Nyorere; , Uguru Hilary (Archives of Current Research International, 2019)
The compressive behaviours (compressive strength, compressive energy, Young’s modulus, failure time, and compressive strain) of epoxy composite board, reinforced with oil bean pod shell particulates (OBPS) and mahogany timber saw dust (SD) were investigated in this research. The samples were prepared with five different fillers (OBPS and SD) percentage (10, 15, 20, 25 and 30 vol.%) in the ratio of 1:1. Both filler materials where treated with 5(w/v)% Sodium hydroxide solution to enhance their mechanical properties. All the composite samples were tested according to ASTM standards, by using the Universal Testing Machine. Results obtained from the research showed that fillers loading had significant (P ≤0.05) effect on all the compressive behaviours investigated. In addition, the results showed that the fillers significantly improved all the compressive parameters. The compressive strength of the composite increased from 14.54 to 48.19 MPa, as the fillers loading increased from 10 to 30 wt.%, while the Young’s modulus increased by 49%. The compressive energy increased from 21.4 to 146 Nm. Data gotten from this research can be useful in the production of composite boards for engineering applications.